Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Masa Pandemi Covid-19 Di Kelurahan Ngantru - Madin Hilala Krisdayanti; Krissantina Eferyn; Bothy Dewandaru (Asosiasi Dosen Akuntansi Indonesia, 2021)
Coronavirus is a new type of coronavirus that is transmitted to humans. As of September 29, 2012, 1.96 million people were infected. This number is increasing. It should be a concern for everyone to remain vigilant and from now on prioritize PHBS. In this effort to prevent the spread of Covid-19, understanding and habits of PHBS have a very important role in preventive and promotive such as education and community-based prevention in breaking the chain of spread of Covid-19. This is the basis for the community service team to conduct education. The methods used start from the stage of preparation, implementation, evaluation. The implementation of education went very well. The hope is that this education will be held to posyandu cadres will be able to convey to the community at large related to PHBS, especially in the household environment.